A Case Study of Applying Weighted Least Squares to Calibrate a Digital Maximum Respiratory Pressures Measuring System - Ferreira, José L.; Vasconcelos, Flávio H.; Tierra-Criollo, Carlos J. (IntechOpen, 2011)
None